Mill and the Law of Markets: Comment - Hunter, Laurence C. (Quarterly Journal of Economics, 1960)
Journal Article Mill and the Law of Markets: Comment Get access Laurence C. Hunter Laurence C. Hunter University of Manchester Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 74, Issue 1, February 1960, Pages 158–162, https://doi.org/10.2307/1884140 Published: 01 February 1960